2021
DOI: 10.1158/1078-0432.ccr-20-4300
|View full text |Cite
|
Sign up to set email alerts
|

High PDGFRb Expression Predicts Resistance to Radiotherapy in DCIS within the SweDCIS Randomized Trial

Abstract: Purpose: This study analyzes the potential of stromal platelet-derived growth factor receptor-beta (PDGFRb) expression as biomarker for radiotherapy (RT) benefit on ipsilateral breast events (IBE) in ductal carcinoma in situ (DCIS). Improved identification of DCIS patients refractory to adjuvant whole-breast RT is needed. Predictive biomarker studies in DCIS have focused on tumor cell features rather than the tumor-associated stroma, despite growing evidence of its influence on therapy effici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…PDGFR‐β participates in the regulation of the cell function of fibroblasts, and PDGFR‐β + CAFs are associated with a worse prognosis in pancreatic cancer. 33 , 34 , 35 , 36 , 37 , 38 In line with these reports, we found that PDGFR was highly expressed in CAFs but was rarely expressed in PDAC tumor cells. Further results showed that knockdown of LINC00460 increased the proliferation of CAFs and activated the PDGFR signaling pathway, and this effect could be reversed by treatment with crenolanib (PDGFR inhibitor).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…PDGFR‐β participates in the regulation of the cell function of fibroblasts, and PDGFR‐β + CAFs are associated with a worse prognosis in pancreatic cancer. 33 , 34 , 35 , 36 , 37 , 38 In line with these reports, we found that PDGFR was highly expressed in CAFs but was rarely expressed in PDAC tumor cells. Further results showed that knockdown of LINC00460 increased the proliferation of CAFs and activated the PDGFR signaling pathway, and this effect could be reversed by treatment with crenolanib (PDGFR inhibitor).…”
Section: Discussionsupporting
confidence: 90%
“…PDGFR‐α and PDGFR‐β are expressed at similar levels in fibroblasts. PDGFR‐β participates in the regulation of the cell function of fibroblasts, and PDGFR‐β + CAFs are associated with a worse prognosis in pancreatic cancer 33–38 . In line with these reports, we found that PDGFR was highly expressed in CAFs but was rarely expressed in PDAC tumor cells.…”
Section: Discussionsupporting
confidence: 89%
“…In the context of radiation or radiotherapy, there are few or no published records on the effects of radiation on the expression of PDGF and/or PDGFRs in stromal cells. In a recent study by Strell et al performed on mammary ductal carcinoma in situ (DCIS) patient samples, authors found an association between high tissue expression of PDGFR‐β and reduced RT sensitivity, indicating a potential role of PDGFR‐β positive cells in radiotherapy resistance 55 . Results from our study indicate that exposure of CAFs to intermediate or high radiation doses does not have a significant impact on PDGFR‐β expression or signaling in CAFs, suggesting that radiation exposure does not trigger PDGFR‐mediated tumor radioresistance.…”
Section: Discussionmentioning
confidence: 99%
“…RT resistance remains a major cause of failure of clinical cancer therapy [33][34][35]. Knowledge of the mechanisms underlying RT resistance is urgently needed so that patients who have RT-resistant disease (and hence are unlikely to respond to RT) can be spared the morbidity and expense of ineffective treatment, ideally before that treatment is begun.…”
Section: Discussionmentioning
confidence: 99%